2006
DOI: 10.1007/s00330-006-0297-z
|View full text |Cite
|
Sign up to set email alerts
|

Scientific papers presented at the 2000–2001 European Society of Gastrointestinal and Abdominal Radiology (ESGAR) meetings: publication rates during the period 2000–2004

Abstract: The aim of this study was to investigate the rate at which abstracts orally presented at the ESGAR 2000 and 2001 meetings were published between 2000-2004, and to identify predictive factors of publication. The abstracts of ESGAR meeting presentations were reviewed and classified according to organ, modality, type of design, country of origin of the studies and basic categories of diagnostic or interventional. The presentations were searched for publication in Medline-indexed journals using the PubMed server. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 17 publications
4
36
0
6
Order By: Relevance
“…Comparatively, the overall publication rate of 44.9% appears to be higher than previously shown for other international radiology conferences. For example, publication rates for the 1993 American Society of Neuroradiology (ASNR) conference, the 1995 Radiological Society of North America (RSNA) conference, and the 2001 European Society of Gastrointestinal and Abdominal Radiology (ESGAR) conference were 37%, 33% and 40%, respectively (12)(13)(14)(15). The higher rate of publication of presented abstracts at SIR and CIRSE is likely multifactorial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparatively, the overall publication rate of 44.9% appears to be higher than previously shown for other international radiology conferences. For example, publication rates for the 1993 American Society of Neuroradiology (ASNR) conference, the 1995 Radiological Society of North America (RSNA) conference, and the 2001 European Society of Gastrointestinal and Abdominal Radiology (ESGAR) conference were 37%, 33% and 40%, respectively (12)(13)(14)(15). The higher rate of publication of presented abstracts at SIR and CIRSE is likely multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…The date range for manuscript search was from the 2012 conference date until approximately 3 years later (Apr 1,2015). CIRSE was held from September [15][16][17][18][19]2012, and SIR from March 24-29, 2012. The protocol for manuscript search began with PubMed, in which the first authors last name and first initial was used to identify possible articles with a similar title.…”
Section: Data Collectionmentioning
confidence: 99%
“…Abstract presentations at national meetings allow a rapid transfer of knowledge in summarizing current research and focusing future research endeavors (1)(2)(3)(4)(5). In spite of the fact that many studies are of sufficient value for presentation in these sessions, only the most instructive and highest quality studies are worthy of full-text publication in a peer-reviewed journal (2).…”
mentioning
confidence: 99%
“…In a survey of the literature, the publication rate of papers from a variety of specialties ranged between 8.5% and 78% (6). Worldwide, only a few investigations exist concerning radiology meetings, which report rates ranging 11%-47% (1)(2)(3)(4)(5)(6)(7)(8). According to a study evaluating Turkish radiology meetings in years 1995-2002, the overall publication rate was 11% (1).…”
mentioning
confidence: 99%
“…Hence, some authors suggested that the rate of publication of orally presented scientific abstracts might constitute an interesting criterion [1]. Regarding radiology meetings, several investigations reported publication rates ranging from 8% to 47% [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%